1985
DOI: 10.1177/00220345850640031601
|View full text |Cite
|
Sign up to set email alerts
|

Some Physico-chemical Properties of Deciduous Enamel of Children with and Without Pre-natal Fluoride Supplementation (PNF)

Abstract: Physico-chemical investigations of enamel from deciduous teeth of a small number of children with and without pre-natal fluoride supplementation (PNF) exhibited the following differences between the PNF and non-PNF enamel, with the former showing: (a) more homogeneous and less extensive patterns of acid-etching; (b) denser crystal populations in intra-prismatic regions; (c) larger prism dimensions; (d) greater total mineral density (wt%ash); (e) higher degree of crystallinity; (f) smaller a-axis dimensions; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Intake of high concentration of fluoridated milk together with other food and beverages with high fluoride content could cause dental fluorosis especially in children whose enamel is still developing. 35 Toth et al 36 have suggested that under similar experimental conditions, physiological exposure and bioavailability of fluoride in fluoridated salt, milk and tablets are comparable.…”
Section: Discussionmentioning
confidence: 98%
“…Intake of high concentration of fluoridated milk together with other food and beverages with high fluoride content could cause dental fluorosis especially in children whose enamel is still developing. 35 Toth et al 36 have suggested that under similar experimental conditions, physiological exposure and bioavailability of fluoride in fluoridated salt, milk and tablets are comparable.…”
Section: Discussionmentioning
confidence: 98%
“…A hypothesis evolved which suggested that fluoride helped to make the enamel crystal "more perfect", and therefore less acid soluble. Le Geros et al (6) performed a physicochemical investigation of enamel from deciduous teeth. They found that enamel from children who had been subjected to prenatal fluoridation exhibited more homogeneous and less extensive patterns of acidetching, denser crystal populations in intraprismatic regions, larger prism dimensions, greater total mineral density, a higher degree of crystallinity, smaller a-axis dimensions, more fluoride and less carbonate contents.…”
Section: Introductionmentioning
confidence: 99%
“…However, these early indications of the posteruptive effect of fluoride were neglected and the dogma of the pre-eruptive mode of action of fluoride remained the basis for fluoride research. In this context, LeGeros et al [1985] performed physicochemical investigations of enamel from deciduous teeth of a small number of children with and without prenatal fluoride supplementation. They found that enamel from children who were subjected to prenatal fluoridation exhibited more homogeneous and less extensive patterns of acid etching, denser crystal populations in intraprismatic regions, larger prism dimensions, greater total mineral density, a higher degree of crystallinity, smaller a-axis dimensions, more fluoride and less carbonate contents.…”
mentioning
confidence: 99%